Whale distribution in a breeding area:spatial models of habitat use and abundance of western South Atlantic humpback whales - Bortolotto, Guilherme Augusto; Danilewicz, Daniel; Hammond, Philip Steven; Thomas, Leonard Joseph; Zerbini, Alexandre N (Marine Ecology Progress Series, 2017)
The western South Atlantic humpback whale population was severely depleted by commercial whaling in the late 19th and 20th centuries, and today inhabits a human-impacted environment in its wintering grounds off the Brazilian coast. We identified distribution patterns related to environmental features and provide new estimates of population size, which can inform future management actions. We fitted spatial models to line transect data from 2 research cruises conducted in 2008 and 2012 to investigate (1) habitat use and (2) abundance of humpback whales wintering in the Brazilian continental shelf. Potential explanatory variables were year, depth, seabed slope, sea-surface temperature (SST), northing and easting, current speed, wind speed, distance to coastline and to the continental shelf break, and shelter (a combination of wind speed and SST categories). Whale density was higher in slower currents, at shorter distances to both the coastline and shelf break, and at SSTs between 24 and 25°C. The distribution of whales was also strongly related to shelter. For abundance estimation, easting and northing were included in the model instead of SST; estimates were 14264 whales (CV = 0.084) for 2008 and 20389 (CV = 0.071) for 2012. Environmental variables explained well the variation in whale density; higher density was found to the south of the Abrolhos Archipelago, and shelter seems to be important for these animals in their breeding area. Estimated distribution patterns presented here can be used to mitigate potential human-related impacts, such as supporting protection in the population’s core habitat near the Abrolhos Archipelago.